2021
DOI: 10.21873/invivo.12582
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Overall Complications and Remote Infection After Gastrectomy in Elderly Gastric Cancer Patients

Abstract: Background/Aim: A significant predictive factor for the occurrence of complications after gastrectomy in elderly gastric cancer patients is yet to be determined. We aimed to evaluate the clinical factors associated with overall complications including remote infection after gastrectomy in elderly gastric cancer patients. Patients and Methods: We retrospectively analyzed data of 101 patients aged over 80 years, who underwent curative gastrectomy. We analyzed the clinicopathological factors that were independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…However, the study by Nakamura et al . showed that the total complication rate among elderly patients with gastric cancer was 24.8% 23 . Similar results were also found in Yang et al .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the study by Nakamura et al . showed that the total complication rate among elderly patients with gastric cancer was 24.8% 23 . Similar results were also found in Yang et al .…”
Section: Discussionsupporting
confidence: 87%
“…However, the study by Nakamura et al showed that the total complication rate among elderly patients with gastric cancer was 24.8%. 23 Similar results were also found in Yang et al that the rate of the total complications was 13.6%-25%. 24 This can be explained by the fact Hence, our participants had a higher rate of postoperative complications than that previously reported.…”
Section: Discussionsupporting
confidence: 82%
“…1 Recently, with the greater population of elderly people in Japan, the rate of laparoscopic gastrectomy has been rapidly increasing among elderly patients with GC. 3 By contrast, the prevalence rate of postoperative DGE ranges from 5% to 10% based on clinical symptoms. 4,5 Clinically diagnosed DGE is generally a mild condition.…”
Section: Introductionmentioning
confidence: 99%
“…In JCOG 0912, the overall incidence rate of in‐hospital grade 3–4 surgical complications (Clavien–Dindo Classification) was only 3.3% among the patients who underwent LDG 1 . Recently, with the greater population of elderly people in Japan, the rate of laparoscopic gastrectomy has been rapidly increasing among elderly patients with GC 3 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study from the Netherlands5 examined outcomes in octogenarians following major surgical procedures and found that, depending on the diagnosis, they had increased median length of stay, 30-day major morbidity, and 30-day mortality. Additional risk factors for overall complications in elderly patients scheduled for surgery include smoking and alcohol consumption,6 malnutrition,6 excessive polypharmacy,7 mental health disorders (eg, preoperative depression or anxiety),8,9 hemoglobin < 11 g/dl,6,10 diabetes and glycemic control (eg, increased HBA1c) 6. These studies and many others highlight the significant risks associated with surgical and other interventions performed on older and frail individuals, and it has been suggested that prehabilitation may be an important antidote that supports improved outcomes 11…”
Section: Introductionmentioning
confidence: 99%